Digital silence and civic trust: rethinking the Indonesian parliament’s online political communication on sexual violence - Putra, Dedi Kurnia Syah; Abdurrahman, Muhammad Sufyan; Wahyuni, Itca Istia; Wibowo, Lintang Ayu (Frontiers in Communication, 2026)
Amid a surge in gender-based violence, with over 25,000 cases reported by Komnas Perempuan in 2021, a 50 percent increase, and more than 15,000 incidents in 2024, the urgency for transparent and inclusive legislative communication in Indonesia has intensified. The Indonesian Parliament’s official website (DPR.go.id) plays a critical role in bridging the gap between lawmaking and public understanding, particularly regarding the Sexual Violence Crime Law (UU TPKS). Using a qualitative based on interviews, field observations, and document analysis, this study investigates how the Indonesian Parliament’s (DPR) digital communication shapes civic engagement and institutional trust. Applying Ong’s framework of secondary orality, the study evaluates five communicative dimensions—interactivity, dialogic capacity, communal participation, simultaneity, and digitalization. Findings show that while the DPR.go.id provides digital tools, its lack of integration into a responsive framework results in digital silence, limiting meaningful public participation and fostering a trust deficit. The website functions more as a one-way broadcast than a space for reciprocal political communication. This study recommends enhancing feedback mechanisms, real-time engagement, and clearer access to improve public understanding and trust. The research contributes to digital political communication by offering a framework to assess digital platforms’ role in fostering inclusive civic engagement.